Comparing the Cost and Outcomes of Laparoscopic versus Open Appendectomy for Perforated Appendicitis in Children. Issue 9 (September 2013) - Groves, Leslie B; Ladd, Mitchell R.; Gallaher, Jared R.; Swanson, John; Becher, Robert D.; Pranikoff, Thomas; Neff, Lucas P.
Although laparoscopic appendectomy (LA) is accepted treatment for perforated appendicitis (PA) in children, concerns remain whether it has equivalent outcomes with open appendectomy (OA) and increased cost. A retrospective review was conducted of patients younger than age 17 years treated for PA over a 12.5-year period at a tertiary medical center. Patient characteristics, pre-operative indices, and postoperative outcomes were analyzed for patients undergoing LA and OA. Of 289 patients meeting inclusion criteria, 86 had LA (29.8%) and 203 OA (70.2%), the two groups having equivalent patient demographics and preoperative indices. Inpatient costs were not significantly different between LA and OA. LA had a lower rate of wound infection (1.2 vs 8.9%, P = 0.017), total parenteral nutrition use (23.3 vs 50.7%, P < 0.0001), and length of stay (5.56 ± 2.38 days vs 7.25 ± 3.77 days, P = 0.0001). There was no significant difference in the rate of postoperative organ space abscess, surgical re-exploration, or rehospitalization. In children with PA, LA had fewer surgical site infections and shorter lengths of hospital stay compared with OA without an increase in inpatient costs.